2013
DOI: 10.5817/sts2013-2-11
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Analysis of Free Technique Cross Country and Skating on Roller Skies

Abstract: Abstrakt:Od

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Several studies have been performed to investigate physiological aspects (Hoffman et al, 1998;Saltin, 1997;Staib, Im, Caldwell, & Rundell, 2000), fewer studies -kinematic and kinetic aspects (Hoffman et al, 1995;Holmberg et al, 2005;Horyna, Finková, & Kračmar, 2012;Millet, Hoffman, Candau, & Clifford, 1998;Smith, Fewster, & Braudt, 1996) and very few studieskinesiological aspects (Chrástková, Bačáková, Špulák, Kračmar, & Čmejla, 2012;Chrastkova, Bacakova, Spulak, Cmejla, & Kracmar, 2013;Holmberg et al, 2005;Horyna, Bačáková, Špulák, Kračmar, & Čmejla, 2014;Suchý & Kračmar, 2008;Zoppirolli et al, 2013) of the DP technique. Holmberg et al (2005) showed that muscles were engaged in sequential order starting with trunk and hip flexors, followed by shoulder extensors and the elbow extensor triceps brachii during DP.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed to investigate physiological aspects (Hoffman et al, 1998;Saltin, 1997;Staib, Im, Caldwell, & Rundell, 2000), fewer studies -kinematic and kinetic aspects (Hoffman et al, 1995;Holmberg et al, 2005;Horyna, Finková, & Kračmar, 2012;Millet, Hoffman, Candau, & Clifford, 1998;Smith, Fewster, & Braudt, 1996) and very few studieskinesiological aspects (Chrástková, Bačáková, Špulák, Kračmar, & Čmejla, 2012;Chrastkova, Bacakova, Spulak, Cmejla, & Kracmar, 2013;Holmberg et al, 2005;Horyna, Bačáková, Špulák, Kračmar, & Čmejla, 2014;Suchý & Kračmar, 2008;Zoppirolli et al, 2013) of the DP technique. Holmberg et al (2005) showed that muscles were engaged in sequential order starting with trunk and hip flexors, followed by shoulder extensors and the elbow extensor triceps brachii during DP.…”
Section: Introductionmentioning
confidence: 99%